2020
DOI: 10.5944/rppc.26460
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo unificado para el tratamiento transdiagnóstico de los trastornos emocionales en adolescentes a través de internet (iUP-A): Aplicación web y protocolo de un ensayo controlado aleatorizado

Abstract: Internet-delivered unified protocol for transdiagnostic treatment of emotional disorders in adolescents (iUP-A): Web application and study protocol for a randomized controlled trial. A characteristic of transdiagnostic treatment is that it targets simultaneously the core symptoms and underlying vulnerabilities of several disorders. The UP-A is a new empirically supported cognitive-behavioral therapy (CBT) protocol developed by Ehrenreich-May’s group for the transdiagnostic treatment approach of emotional disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…Moreover, the lack of training in evidence-based treatments among professionals further adds to this problem [ 114 ]. Finally, in Spain, several RCTs have been conducted using the internet to provide evidence-based treatments, showing that they are effective for the treatment of ED and, in particular, depression, in community samples [ 94 ] and primary care [ 115 , 116 ], and others are underway [ 117 ]. This study demonstrated that an internet-delivered protocol for ED was effective in public specialized care, a setting with a high demand, but much less explored, thus adding to the literature on these treatments for ED.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lack of training in evidence-based treatments among professionals further adds to this problem [ 114 ]. Finally, in Spain, several RCTs have been conducted using the internet to provide evidence-based treatments, showing that they are effective for the treatment of ED and, in particular, depression, in community samples [ 94 ] and primary care [ 115 , 116 ], and others are underway [ 117 ]. This study demonstrated that an internet-delivered protocol for ED was effective in public specialized care, a setting with a high demand, but much less explored, thus adding to the literature on these treatments for ED.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were adolescents selected to participate in an internet-delivered version of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Adolescents (iUP-A; Sandín et al, 2019Sandín et al, , 2020b who were recruited through school counselors' referrals from four secondary schools in Castilla-La Mancha and Madrid (Spain). In order to be able to participate in the study, adolescents had to be between 12 and 18 years old, reside in Spain and have access to a computer or tablet.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical diagnoses were conducted by means of the MINI [26,27]. The questionnaires EAN [30], CDN [30], and the total score on the RCADS-30 [31] were used as primary outcome measures.…”
Section: Instrumentsmentioning
confidence: 99%
“…Several meta-analyses have shown that T-iCBT protocols could be effective in the reduction of anxious and depressive symptomatology [9,25]. Recently, our group has developed an internet-based version of the UP-A (i.e., the iUP-A) [26]. As far as we know, this is the first T-iCBT treatment that targets anxiety and depression in adolescents, as well as the first adaptation of the UP-A into a web-based or online format.…”
Section: Introductionmentioning
confidence: 99%